O RECURSO DO MÉTODO – UMA LEITURA INTERTEXTUAL - Pereira, Tatiana Selva (Organon, 2004)
This essay studies the Cuban novel El Recurso del Método by the Cuban novelist Alejo Carpentier,precursor of the “marvelous realism” in the Americas from a comparative perspective of literary theories andnotions such as intertextuality, the cultural decolonization process, deterritorialization, literary and culturalhybridism and the search for cultural identity within the historical, social and political framework ofCarpentier’s literary rendering. Some fundamental notions about the historical evolution of comparativeliterature are dealt with to better comprehend the importance of Carpentier’s literary work, his contribution to agenuine Latin American identity as well as the inclusion of this peripheral literature into the world literature.Providing some examples of this literary device present in the novel, the origin and definition of the so-called“marvelous reality” are focused. The intertextual nature of Carpentier’s text and its carnavalized discourse, itshybrid features and the transcultural issues are outlined in this essay as well.